V Hudi luknji straši! – Sodobne povedke o prikazni in njihov kontekst Huda luknja Gorge is a Haunted Place! – Contemporary Legends about a Vanishing Lady and Their Context - Kvartič, Ambrož (Studia mythologica Slavica, 2012)
<span style="line-height: 115%; font-family: ’Calibri’,’sans-serif’; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ’Times New Roman’; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Although narratives of a ghost in Huda luknja gorge show textual parallels with an international migratory legend type called ‚vanishing hitchhiker‘, their meaning is clearer when studied as contextualized legends, embedded in the time and space of Huda luknja. Legends about a vanishing lady dressed in black or white have always been adapting to their surrounding socio-historical situation, and were crucially shaped by the establishment of high-school programs in the towns of Velenje and Slovenj Gradec and by cancellation of a railroad connection between Velenje and Dravograd. These events redefined processes of migration through the gorge – especially the migration of young people, who are the most prominent group of the legend‘s tellers.